Genome-wide analysis of deoxyribonucleic acid in endometrial cancer using comparative genomic hybridization microarrays. Issue 2 (1st March 2006) - O'toole, S A; Dunn, E.; Sheppard, B. L.; Klocker, H.; Bektic, J.; Smyth, P.; Martin, C.; Sheils, O.; O'leary, J J
Abstract : The aim of this study was to identify amplified oncogenes in endometrial cancer using array-based comparative genomic hybridization (array CGH). Despite its prevalence, the molecular mechanisms of endometrial carcinogenesis are still poorly understood. The selected array CGH allows the simultaneous examination of 58 oncogenes commonly amplified in human cancers and is capable of achieving increased mapping resolution compared with conventional CGH. A subset of 8 specimens from a bank of 60 malignant and normal specimens was selected for array analysis to identify potential genes of interest. TaqMan polymerase chain reaction was carried out on the 60 specimens to examine if aberrations at the genomic level correlated with gene expression and to compare expression in normal and malignant samples. Oncogenes amplified in the endometrial cancers included AR, PIK3CA, MET, HRAS, NRAS, D17S1670, FGFR1, CTSB, RPS6KB1, LAMC2, MYC, PDGFRA, FGF4/FGF3, PAKI, and FGR. Three genes were examined at the messenger RNA level. AR and PIK3CA were higher in normal specimens, and MET was higher in malignant samples, suggesting a role for MET in endometrial cancer. Newer arrays examining more genes and larger sample numbers are necessary to elucidate the carcinogenic pathway in endometrial cancer.